Comparative Economics of Silvopasture, Hortipasture and Annual Crops on Marginal Agricultural Lands of Arid Zone of Rajasthan - Gajja, B L; Bhati, T K; Harsh, L N; Khan, M S (Annals of Arid Zone, 2016)
An attempt was made to study the alternative cropping systems in arid zone of Rajasthan, in comparison to arable farming, The silvopasture based livestock grazing system (silvopastoral systems), hortipasture and arable farming were compared. The silvopastoral and hortipasture systems were more profitable than arable farming system at 12 and 20% discount rates. Sensitivity analysis, further, confirm the results, However, the silvopastoral system' with sheep grazing at 20% discount rate is not viable in mostcases. Under new economic policy and GATT agreement, the alternative farming system is considered to be more viable, which would not only improve" the living standard of the region but also improve the ecological balance and sustainability of the arid zone of Rajasthan.